Correct Botanical Identity of some Established Old Exotics in Himachal Pradesh - Kumar, Adarsh; Hingorani, G. R. (Indian Forester, 1973)
The paper gives tbe correct botanical identity of twenty nine established exotics growing around Simla and Manall (Himachal Pradesh). It also gives in brief the botanical description, natural distibution. locality where introduced, year of planting (if available) height, and girth of the exotic species.